Intelligent single-axis solar tracking system for enhanced energy harvesting efficiency - Adnan M. Al-Smadi; Deema Al-Shogran; Hazem Jihad Badarneh (Institute of Advanced Engineering and Science, 2026)
The need for efficient clean energy solutions has increased due to population growth, climate change, and the development of industries. Among these, the most valuable clean and sustainable alternative is solar energy, i.e., photovoltaic (PV) technology. However, the key challenge is represented by maximizing the PV systems' efficiency. This paper proposes an IoT-enabled single-axis solar tracking system for improving PV by constantly aligning solar panels with the trajectory of the sun. To achieve that, an Arduino microcontroller is integrated with light-dependent resistors (LDRs). LRDs perform real-time detection of solar irradiance in order to adjust along with the azimuth axis. Based on the experimental results, the IoT-enabled single-axis solar tracking system improves energy harvesting by comparing with fixed-tilt PV. The proposed system outperforms the fixed-tilt PV by 22.5% in daily energy yield and average power output. Furthermore, tracking efficiency is better than fixed-tilt PV by 96.3% and tracking error of 3.7%.